Internal tides off the Amazon shelf – Part 1: The importance of the structuring of ocean temperature during two contrasted seasons - F. Assene; F. Assene; A. Koch-Larrouy; I. Dadou; M. Tchilibou; G. Morvan; J. Chanut; A. Costa da Silva; V. Vantrepotte; D. Allain; T.-K. Tran (Ocean Science, 2024)
The impact of internal and barotropic tides on the vertical and horizontal temperature structure off the Amazon River was investigated during two highly contrasted seasons (AMJ: April–May–June; ASO: August–September–October) over a 3-year period from 2013 to 2015. Twin regional simulations, with and without tides, were used to highlight the general effect of tides. The findings reveal that tides have a cooling effect on the ocean from the surface (∼ 0.3 ∘C) to above the thermocline (∼ 1.2 ∘C), while warming it up below the thermocline (∼ 1.2 ∘C). The heat budget analysis indicates that the vertical mixing is the dominant process driving temperature variations within the mixed layer, while it is associated with both horizontal and vertical advection to explain temperature variations below. The increased mixing in the simulations including tides is attributed to breaking of internal tides (ITs) on their generation sites over the shelf break and offshore along their propagation pathways. Over the shelf, mixing is driven by the dissipation of the barotropic tides. In addition, the vertical terms of the heat budget equation exhibit wavelength patterns typical of mode-1 IT. The study highlights the key role of tides and particularly how IT-related vertical mixing shapes the ocean temperature off the Amazon. Furthermore, we found that tides impact the interactions between the upper ocean interface and the overlying atmosphere. They contribute significantly to increasing the net heat flux between the atmosphere and the ocean, with a notable seasonal variation from 33.2 % in AMJ to 7.4 % in ASO seasons. This emphasizes the critical role of tidal dynamics in understanding regional-scale climate.